THE EFFECT OF INVESTMENT, UNEMPLOYMENT, MINIMUM WAGES ON LABOR ABSORPTION IN WEST JAVA PROVINCE 2008-2020 - Uswatun Hasanah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Economic development has an important objective which is to provide it with sufficient job opportunities in order to pursue economic growth in an area. This study aims to find out and be able to produce an analysis of the effect of investment, unemployment and minimum wages on employment in West Java Province. Secondary data is the data used in this study with multiple linear regression analysis tools and processing using SPSS 23. Then it is produced thatThe research and discussion above can be partially concluded that the minimum wage variable has a significant effect on employment, then investment and unemployment variables have no significant effect. Meanwhile, investment, unemployment and minimum wage variables simultaneously have a significant effect on employment.